Grade prediction improved by regular and maximal association rules - Udristoiu, Anca Loredana; Udristoiu, Stefan (International Journal of Intelligent Systems and Applications in Engineering, 2015)
In this paper we propose a method of predicting student scholar performance using the power of regular and maximal association rules. Due to the large number of generated rules, traditional data mining algorithms can become difficult and inappropriate to educational systems. Thus, we use some methods to overcome this problem, discovering rules useful in educational process. These methods are applied to the e-learning system Moodle, for âDatabaseâ course.